The role of sports media in covering sports competitions and events Field Study on students of institute of science and technologies of physical and sport activities M'sila - djalal.merniz,; بوسكرة احمد, (sports creativity, 2025)
The aim of this study is to describe the role of sports media in covering stap student sporting events and competitions in order to understand the relationship between sports media and students of scientific institutes and physical and sports activity techniques, their interests in sports competitions, sporting events and media relations, as examples of sporting events and competitions of different types and the purpose of this study is to describe the role of sports media in covering high school student sporting events and competitions in order to understand the relationship between sports media, students of scientific institutes and activity techniques their interests in sports competitions, sporting events and media relations, as examples of sporting events and competitions of different types, and to try to clarify the role played by these to meet information needs by providing the public with information and information about sporting events, in addition to providing information and knowledge, as well as meeting the needs of the public. the researcher found that the diversification of information and attention focused more on the types of topics centred on major sporting events without turning a blind eye to the rest of the events, as they occupy the opinion of some others groups in society. Increase the size of local and international sporting events in all disciplines and process them more, work on transferring and disseminating the largest amount of information about current sporting events.